Análise legal e técnico-científica de projetos de restauração da flora na microrregião de São João del-Rei, MG - Gonçalves, Wendel do Nascimento (2017)
Considering the history of unsuccessful and ineffective projects in ecological restoration in Brazil, together with the high anthropogenic pressure on natural ecosystems, it is necessary to know and evaluate forest restoration projects according to technical and legal criteria available. In this context, the purpose of this study was to evaluate the quality of the forest restoration projects of environmental regularization processes formalized by the Regional Nucleus of Environmental Regularization of São João del Rei, microregion of Campo das Vertentes / MG. For this purpose, all the projects linked to the regularization processes formalized in the years of 2012, 2013, 2014 and 2015 were analyzed. The data were organized through the use of indicators, whose items were associated to numerical indexes and structured in order to satisfy the two groups of research indicators: indicators related to environmental legislation and environmental technical indicators elaborated by consulting technical and scientific work and subsequent validation by specialists. Through the analyzes, it was observed that most of the Forest Restoration Projects (75.61%) presented an average agreement with the legislation, which characterized the partial noncompliance of Annex I of the Normative Deliberation of COPAM nº. 076/2004. The failures were more recurrent in the identification and evaluation of the physical and biological damages of the area to be restored (IL 3 e IL 4). On the other hand, the great majority of the projects complied with the legal norms in relation to the delimitation, with geographical coordinates, of the area to be restored (IL 5) and also in the presentation of the method and form of implantation of the activities of restoration (IL 6). Almost all of the Forest Restoration Projects (95.12%) presented very low agreement with the environmental technical indicators / parameters, which characterized the lack of knowledge and / or application of the parameters formulated based on the scientific literature. With the exception of ITA 4, for the other indicators, all or almost all of the projects presented low or very low agreement of the Index of Environmental Technical Agreement of the Indicator. Even for ITA 4, which presented the best result, serious failures were also observed, since 100% of the projects did not identify the ecological filters / barriers present in the area to be restored, not considering the guidelines contained in the literature. The general analysis of the results showed the need to reformulate the criteria used by the professionals in the elaboration of the projects, which must fully comply with the parameters of the legislation and present forest restoration projects with greater scientific base.